The Representation of Motivational Values in The Issue of Motivation on Pinterest Website A Semiotic Study - Tantra Afianto Afianto (Universitas Pendidikan Indonesia (UPI), 2014)
This study investigated the representation of motivational values in pictures and the myths underlying the representations. The data are ten pictures containing the issue of motivation retrieved from Pinterest website. This is a qualitative research framed in Barthes’ orders of signification theory (1972). The theory was used to discover the representation of motivational values while the theory of motives by Murray (2009) became the foundation in revealing the myths from the representations. The result shows that there are three classifications of the representation of motivational values, namely the motivational values in global context, the motivational values in the context of health, and the motivational values in the context of sport. Moreover, of the three motivational values, there are five values that stand out: hard work, independence, total action, focus, and benefit of having opportunities. With regard to the myth, there are two motives, namely the motive of achievement and the motive of counteraction. In addition, there are three elaborations in the motive of achievement: to overcome obstacles, to accomplish something difficult, and to master physical things. Furthermore, there are two elaborations in the motive of counteraction: to overcome weaknesses and to repress fear. This study suggests that besides motivational speech of particular people, any texts including pictures can serve as source for motivation.Keywords: Representation, Motives, Motivational values, Myths, Pinterest